CAUSES AND EFFECTS OF TEACHER’ PROFESSIONAL BURN-OUT - Ilona Tandzegolskiene-Bielaglove (PUPIL: International Journal of Teaching, Education and Learning, 2026)
At the second half of the 20th century, psychologist H. J. Freudenberger (1974) was the first to study the phenomenon of professional burnout and revealed the connection between this syndrome and mental-physical exhaustion. The author investigated the personality factors of health care workers and their manifestations, paying great attention in his work to people’s emotional exhaustion and loss of motivation to work. Next, one of the best-known researchers in this field - social psychologist Maslach (2003) - was interested in this phenomenon and developed personal research. The researcher’s work was focused specifically on the emotional state of persons working in the service sphere. Moreover, this researcher, speaking about professional burnout, emphasized the prolonged reaction of the process itself to constantly recurring stressors of various types at work. In the literature, there are various definitions of the phenomenon of professional burnout. The burnout syndrome itself is relevant and very widely studied, although there is no unified description of this syndrome as a phenomenon in the scientific literature. However, there is unanimous agreement on the three components of the burnout syndrome, such as emotional exhaustion, depersonalization and a decrease in self-realization. In the context of changes in education, it is very important to understand and recognize the problems of the pedagogue in time, because the professional burnout syndrome begins imperceptibly and later causes serious consequences for the pedagogue himself/herself, the entire educational process and its management. Though the burnout of pedagogues in preschool education institutions is a relevant problem, still there is a lack of research that reveals how professional burnout affects the professional activities of preschool teachers and what influence it has on the management of the educational process in preschool education institutions. Research questions: What are the manifestations of professional burnout and what are the reasons for its occurrence? What do pre-school teachers experiencing professional burnout go through? How does professional burnout affect the professional activities of preschool teachers? How does the professional burnout of educators affect the management of the preschool education process? Research object - The impact of teachers’ professional burnout on the management of the educational process. The purpose of the study is to evaluate the impact of the professional burnout syndrome of pedagogues on the management of the educational process. An analysis of scientific literature and a mixed research strategy were chosen for the research, including the collection, analysis and interpretation of quantitative and qualitative data. A mixed research strategy was used in this case to highlight a multifaceted approach to the phenomenon under study and to expand the results of the quantitative research while relying on the qualitative research results. During the research, it became clear that professional burnout is a complex phenomenon, manifested by increasing emotional and physical fatigue, depersonalization and reduced professional aspirations. A quantitative study revealed that the age, qualification category and working hours of educators have an impact on professional burnout. It was established that one in seven preschool teachers experience severe professional burnout. The relationship between emotional exhaustion and depersonalization has also been established, suggesting that emotional exhaustion can promote depersonalization. A qualitative study revealed that the causes of professional burnout of teachers working in a preschool education institution are usually associated with organizational factors, such as heavy workloads, conflicting professional relationships and a large number of children in groups. Burnout among preschool teachers has a direct impact on interactions with children, parents, colleagues, and administrators. Professional burnout not only reduces teachers’ motivation to work and their ability to organize activities, but also urges them to give up their position in the organization. Professional burnout also affects the quality of the educational process, creating an unfavourable learning environment and increasing the workload of the remaining employees.